2020
DOI: 10.1371/journal.pntd.0008464
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma haematobium infection is associated with lower serum cholesterol levels and improved lipid profile in overweight/obese individuals

Abstract: Infection with parasitic helminths has been reported to improve insulin sensitivity and glucose homeostasis, lowering the risk for type 2 diabetes. However, little is known about its impact on whole-body lipid homeostasis, especially in obese individuals. For this purpose, a crosssectional study was carried out in lean and overweight/obese adults residing in the Lambaré né region of Gabon, an area endemic for Schistosoma haematobium. Helminth infection status, peripheral blood immune cell counts, and serum met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 41 publications
1
27
1
Order By: Relevance
“…stercoralis infection ( Fig 3 ). These findings are contrary to previous work conducted in schistosomiasis [ 8 , 19 , 37 ], opisthorchiasis [ 47 ] and soil-transmitted helminths [ 48 ], which have all reported that infection with parasites could lead to changed serum lipid levels (LDL-C and/or HDL levels,) or BMI, which in turn helps to prevent the development of disease complications [ 21 , 49 ]. These differences might be a consequence of differing participant age groups, recently of infection, worm burdens, geographical area, culture, and dietary habits.…”
Section: Discussioncontrasting
confidence: 99%
“…stercoralis infection ( Fig 3 ). These findings are contrary to previous work conducted in schistosomiasis [ 8 , 19 , 37 ], opisthorchiasis [ 47 ] and soil-transmitted helminths [ 48 ], which have all reported that infection with parasites could lead to changed serum lipid levels (LDL-C and/or HDL levels,) or BMI, which in turn helps to prevent the development of disease complications [ 21 , 49 ]. These differences might be a consequence of differing participant age groups, recently of infection, worm burdens, geographical area, culture, and dietary habits.…”
Section: Discussioncontrasting
confidence: 99%
“…Normally, miR-122 is highly expressed in the liver, where it constitutes 70% of the total miRNA pool ( Jopling, 2012 ), and plays a pivotal role in liver biology and disease ( Bandiera et al., 2015 ). The result suggests that S. japonicum infection may be associated with significantly altered functions of host livers ( Hu et al., 2020 ), whereas S. haematobium infection reduces the levels of cholesterol-rich lipoprotein species in overweight infected individuals and lower the risk of cardiometabolic diseases ( Zinsou et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol reduction induced by parasitosis has been reported in humans. Natural infection with S. haematobium in obese individuals has a beneficial effect because it reduces the risk of developing cardiometabolic diseases [ 28 ]. Authors propose that the mechanism of the normalization of the lipid profile is due to the use of lipids in the synthesis of lipoproteins for the eggs of S. haematobium .…”
Section: Discussionmentioning
confidence: 99%